5 de febrero: huelga policial, saqueos e incendios en Lima - Quijano, Manuel Valladares (2005)
The events that unfolded in Lima on February 5°, 1975, unsettled General Juan Velasco's military regime, laying bare its weaknesses. Indeed, since them-against the backdrop of the world capitalist crisis-it became evident that the reformist process had come to an end, and that the conflicts within the armed forces had reached a point of high tension. Also, the February 5° events heralded the inminent advent of a new government that offically would close the reformist period.